The cross-border shoppers' behaviour: the case of Singapore. (22nd August 2008) - Hui, Tak Kee; Wan, David
Cross-border shopping has been of interest in the past decade. Given the close proximity of Singapore and Johor Bahru (JB) (located at the southern tip of Malaysia), outshopping has become a notable feature of cross-border visits. We compared the travel frequencies of 203 Singapore residents who travelled to Malaysia for shopping purposes. We also identified and measured the factors that might influence their cross-border shopping behaviour. Our results revealed that there was a significant difference in the travel frequencies between the younger and older respondents. However, there were no significant differences between males and females and between the low income earners and the high income earners. As for the determinants of outshopping behaviour, it was found that marketing mixes and accessibility, as well as economical factors, all had significant and positive influences on cross-border shopping.